The role of community and culture in abortion perceptions, decisions, and experiences among Asian Americans - Chandrasekaran, Sruthi; Key, Katherine; Ow, Abby; Lindsey, Alyssa; Chin, Jennifer; Goode, Bria; Dinh, Quyen; Choi, Inhe; Choimorrow, Sung Yeon (Frontiers in Public Health, 2023)
Introduction: Culture and community can play a role in views, stigma, and access related to abortion. No research to date has documented the influence of culture and community attitudes on Asian American (AA) experiences accessing abortion care in the United States (US). This paper aims to fill gaps in research and understand how cultural and community views influence medication abortion access and experiences among AAs. Methods: We used a community-based participatory research approach, which included collaboration among experts in public health, advocates, practitioners, and community partners to understand abortion knowledge, attitudes, and experiences among AAs. Using a semi-structured interview guide, we interviewed twenty-nine eligible people of reproductive age over 18 that self-identified as Asian American or mixed race including Asian American, Native Hawaiian, and/or Pacific Islander (AANHPI), and had a medication abortion in the US between January 2016 and March 2021. Interviews were analyzed and coded in NVivo 12 using a modified grounded theory approach. Results: Participants described various influences of religion negatively impacting acceptability of abortion among their family and community. Lack of openness around sexual and reproductive health (SRH) topics contributed to stigma and influenced most participants’ decision not to disclose their abortion to family members, which resulted in participants feeling isolated throughout their abortion experience. When seeking abortion care, participants preferred to seek care with providers of color, especially if they were AANHPI due to past experiences involving stigma and judgment from White providers. Based on their experiences, respondents recommended ways to improve the abortion experience for AAs in the US including,1) more culturally aware abortion providers from one’s community who better understand their needs; 2) clinics providing abortion services located in or near AA communities with signage in local languages; and 3) tailored mental health resources with culturally aware therapists. Conclusion: This study demonstrates ways in which culture and community opinions toward SRH can influence both the acceptability of abortion and experiences seeking abortion care among AAs. It is important to consider how family and community dynamics among AAs to better tailor services and meet the needs of AAs seeking abortion care in the US.